2021
DOI: 10.29399/npa.27419
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy in Treatment of Bipolar Disorder

Abstract: Biological underpinnings (i.e., “bio” of bio-psycho-social approach) of Bipolar Disorder (BD) comes to the forefront when addressing its etiology and treatment. However, it is a condition that is challenging to manage with medication, and often the medication alone is insufficient since the symptoms of the disease have different episode characteristics. When the prevalence and inefficacy of drug treatments are considered together, the cruciality of psychosocial interventions in the treatment of the is undeniab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…CBT is recommended for the prevention of depressive or manic episodes and increasing treatment compliance of the pa-tients. Although studies have not reached the best point targeted in BD, CBT is one of the approaches that will provide the clearest contribution to the goal of relieving the suffering of patients and improving their lives [20]. Family therapy in BD will lower the patient's risk of recurrences and functional psychosocial impairment, improve health, and reduce and optimize socioeconomic resources [21].…”
Section: Discussionmentioning
confidence: 99%
“…CBT is recommended for the prevention of depressive or manic episodes and increasing treatment compliance of the pa-tients. Although studies have not reached the best point targeted in BD, CBT is one of the approaches that will provide the clearest contribution to the goal of relieving the suffering of patients and improving their lives [20]. Family therapy in BD will lower the patient's risk of recurrences and functional psychosocial impairment, improve health, and reduce and optimize socioeconomic resources [21].…”
Section: Discussionmentioning
confidence: 99%
“…Electroconvulsive therapy has been found to be effective in treating acute suicidality 82 . Although CBT has been shown to reduce suicidal behaviour in major depressive disorder, such effects are not established in bipolar disorder 102 .…”
Section: Suicidalitymentioning
confidence: 99%
“…Multiple studies reported that the psychotherapeutic approach with close relatives, fellow or kin support, in addition to medication, improves cognitive performances and enhances self-dependency skills among BD cases [11,[114][115][116]. Psychological treatment options, especially cognitive behavioral therapy, are potentially effective in managing depressive events [117][118][119]. Several studies revealed that psychoeducation is more helpful among patients with manic symptoms of BD.…”
Section: Role Of Psychotherapy In Bipolar Mood Disordermentioning
confidence: 99%